Perencanaan Enterprise Architecture Sistem Informasi pada Akademik: Studi Literatur - Phan, Nando; Kristianto, Aditya; Kendrico, Jovin; Alexander, Winar Joko (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The progress of time and rapid technological advancements have driven higher education institutions and other educational organizations to adopt Enterprise Architecture (EA) as a strategic approach to planning and managing their information systems. EA planning begins with an in-depth analysis of the academic literature study environment, including a deep understanding of the needs and challenges faced. Subsequently, business requirement mapping is conducted to identify the strategic goals and objectives that the information system must achieve. Structured approaches like TOGAF (The Open Group Architecture Framework) are often used as a guide in EA planning to ensure consistency and sustainability of the information system. Additionally, it is important to note that EA planning does not solely focus on technical aspects but also involves organizational, human, and process aspects. This includes mapping roles and responsibilities in information system management, developing the skills and capabilities of human resources, and designing effective business processes. By adopting Enterprise Architecture planning for academic literature studies, educational institutions can optimize the use of information technology to enhance efficiency, productivity, and quality in the learning and research processes. EA also enables better integration between existing information systems and future systems, allowing institutions to be better prepared for future challenges.